Knowledge level of Farmers about Improved Rice Cultivation Technology - Dwarka Prasad , L. S. Bareth , Hemant Kumar Jhingoniya , Amit Kumar Keshri; Suman Sharma (Indian Journal of Extension Education, 2015)
The study was conducted in Hanumangarh district of Rajasthan as the district contributes highest area and production of rice crop as compared to other district of Sriganganagar region. Three panchayat samities were selected from district having highest area under rice crop and demonstrations were conducted under MMAabout improved package of practices of rice crop. The Department of Agriculture, Govt. of Rajasthan has conducted demonstration on improved package of practices of rice cultivation technology in these twelve villages under MMA scheme. All the respondents who had participated in demonstration on improved package of practices of rice cultivation technology were called as beneficiary. Equal numbers of non- beneficiary farmers, who did not participate in the demonstrations, from each selected villages were also selected to make the study comparable. In all 210 respondents were included for the study purpose out of which 50 per cent i.e. 105 were beneficiaries and remaining 105 non-beneficiaries. Data were collected by personal interview method. The results revealed that beneficiary farmers possessed more knowledge than the non-beneficiary farmers. The significant difference was observed in the knowledge level of beneficiary and non-beneficiary farmers.